Elucidating the Memory Effects of Magnetic Water Treatment via Precipitated Phase Changes of Calcium Carbonate - Aly Ahmed Mohamed Sayed; Soumya Basu; Takaya Ogawa; Keito Inagawa; Hideyuki Okumura (Eng)
Research on the effects of magnetic fields on water and aqueous solutions has produced various findings, such as the suppression of scale formation in pipes and boilers, inhibition of metal corrosion, enhancement of concrete strength, and changes in properties like viscosity and electrical conductivity. However, the challenges in quantifying these effects, the issues with reproducibility affected by trace elements in the water used in the experiments, and the involvement of complex parameters and mechanisms have led to ongoing debates, with some questioning the very existence of magnetic field effects. The “memory effect”, where the impact of magnetic exposure persists for a certain period, further complicates explanations of these phenomena. To fully elucidate and enable practical applications of these effects, further research is essential. In this study, we aimed to investigate the magnetic field effects on water, including memory effects, where the quantification and elucidation potentially lead to various applications, including environmentally friendly solutions on scale suppression and life science issues. The results revealed that the vaterite phase precipitation ratio significantly increased in magnetically treated water, reaching up to 51%, from 26% without the treatment, which is high reproducibility; furthermore, a reduction in mean particle size was observed when using magnetically treated water, suggesting that it may help prevent scaling. Furthermore, when solutions of calcium carbonate, calcium chloride, and sodium bicarbonate were individually subjected to magnetic treatment, the most notable increase in the vaterite phase precipitation ratio was observed when calcium chloride and sodium bicarbonate solutions were magnetically treated separately and then reacted to precipitate calcium carbonate.